Editorial: Opening for debate and contestation: OECD's International Early Learning and Child Well-being Study and the testing of children's learning outcomes. Issue 1 (January 2019) - Diaz-Diaz, Claudia; Semenec, Paulina; Moss, Peter
This special issue aims to bring critical perspectives to bear on a growing phenomenon in education: comparative assessment of educational performance using standardized measures of outcomes or 'international large-scale assessments'. We focus on one of its latest examples: the International Early Learning and Child Well-being Study. Proposed by the Organisation for the Economic Co-operation and Development (OECD, n.d.a) in 2012, this study is now being put into practice, targeting early childhood education and young children in particular. The articles in this edited collection offer varied critiques of this project as well as critiques of the influential role that the OECD is playing in how member countries design, implement and assess their early childhood education.